Optimize the Time and Network on the Distribution of Tempe Industry by Using the Approach of the Assignment and Networking - Gina Agnia; Dene Herwanto; Ica Hoerunisa; Billy Nugraha; Rianita Puspa Sari (Jurnal Serambi Engineering, 2021)
The problems that occur in the soybean tempe home industry are the competition in the market sector and unstable prices. The purpose of this study is to determine the assignment of employees in performing their works and to distribute them to each destination with the shortest distance. The research method used is assignment, networking using the assistance of the operations management software program - quantitative methods (POM-QM) for windows. The data used are the primary data conducted in a preliminary study. In addition, data collection techniques are carried out in several ways, namely interviews, observation and schedule recording. The finding provides optimal results for all four employees based on suitable jobs. Each employee is employee 1 with a type of laundering taking 17 minutes. Employees 2 with a kneading type of work taking 35 minutes. Eemployees 3 with wrapping job type taking 10 minutes. Meanwhile, eemployees 4 is breawing taking 15 minutes. In addition, the distribution of tempe to the destination point with the shortest route produces a distance of 76 km.